The formation of our Solar System and the planetary diversity of our galaxy - Silva, Stela Ishitani (Cadernos de Astronomia, 2024)
The Solar System is the only one, among the billions of planetary systems predicted in our Galaxy, that is currently known to host life. Home to the Sun, the Moon, Earth, and seven other planets, its formation began approximately 4.56 billion years ago. This paper provides a review of the formation of the Solar System, detailing the key steps in the process, from a cloud of gas in our Galaxy to the birth of the Sun, the formation of planets like Jupiter and Earth, and the origins of smaller celestial bodies such as moons, asteroids, and comets. Current theories are based on observations of our own Solar System as well as studies of other planetary systems with varying ages and locations in the Galaxy. Analyzing our Solar System in the context of other planetary systems highlights how these comparisons are crucial for deepening our understanding of planetary formation and evolution processes.